2007
DOI: 10.1007/s10973-006-8462-9
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis of pure and impurity doped pentaerythritol tetranitrate crystals grown at room temperature

Abstract: Pentaerythritol tetranitrate (PETN) powders are used to initiate other explosives. During longterm storage, changes in powder properties can cause changes in the initiation performance. Changes in the morphology and surface area of aging powders are observed due to sublimation and growth of PETN crystals through coarsening mechanisms, (e.g. Ostwald ripening, sintering, etc.). In order to alleviate the sublimation of PETN crystals under service conditions, stabilization methods such as thermal cycling and dopin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…This value of activation energy for pure PETN is similar to literature values (Burnham et al 2009;Pitchimani et al 2007a). The decrease of activation energy due to doping of Zn ion is consistent with the result found by Pitchimani et al (2007c) for PETN crystal. As the doping concentration increases beyond a certain limit (1,000 ppm) activation energy and A parameter increase again with increasing Zn doping concentration.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This value of activation energy for pure PETN is similar to literature values (Burnham et al 2009;Pitchimani et al 2007a). The decrease of activation energy due to doping of Zn ion is consistent with the result found by Pitchimani et al (2007c) for PETN crystal. As the doping concentration increases beyond a certain limit (1,000 ppm) activation energy and A parameter increase again with increasing Zn doping concentration.…”
Section: Resultssupporting
confidence: 91%
“…A small amount of nitro compound, such as mono-, di-, and trinitrobenzenes, result in decrease in stability at elevated temperatures (Bourjol 1953;Urbanski et al 1935), whereas the addition of small amount of urea stabilizes PETN (WestfalischAnhaltische Sprengstoff 1940). Among the metal ions, Zn was found to be an ideal impurity which when added in a small amount does not change the crystal structure or interact with PETN but changes the surface morphology, evaporation rate, and activation energy (Pitchimani et al 2007b; Pitchimani et al 2007c). In the present study, we have investigated the effect of Zn ion doping concentrations on sublimation rates and activation energy of evaporation of PETN thin films using AFM.…”
Section: Introductionmentioning
confidence: 99%
“…Pitchimani et al. showed that doping with inorganic salt changed the evaporation rate as well as Arrhenius parameters 30. Rogers et al.…”
Section: Resultsmentioning
confidence: 99%
“…Atomic force microscopy (AFM) imaging has revealed morphological changes in the growth center in the presence of impurities [8][9][10]. Impurities have also been shown to alter the thermodynamic properties of singles crystals [11].…”
Section: Introductionmentioning
confidence: 99%
“…Keywords: Single crystal · PETN · Doping · Impurities · Mass-Loss rate · Morphology ous works have demonstrated that doping with appropriate compounds can control such aging process of PETN [11,17,18]. For instance, it was shown that doping with homologs like dipentaerythritol hexanitrate (diPEHN) and tripentaerythritol octanitrate (triPEON) can lower the vapor pressure of PETN single crystals [19].…”
Section: Introductionmentioning
confidence: 99%